Modified Oil Palm Starch As A Potential Binder For Particleboard - Abd Karim, Norani (2017)
This study investigates the potential of oil palm starch extracted from oil palm trunk to be used as binder for particleboard. Two types of oil palm samples were prepared, which was soaked with sodium metabisulphite only with 1000 mL of 0.5 % (w/v) in aqueous solution, and another type of sample used 0.2 % sodium metabisulphite and 0.5 % of lactic acid as a catalyst in oil palm starch extraction methods in order to get higher yields of starch collection. Preliminary studies were also carried out to get optimum condition for the particleboard manufacturing. In this study, the commercial corn starch was used as a comparison for oil palm starch performance.